If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 2x + 17 Reorder the terms: 15 = 17 + 2x Solving 15 = 17 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + -2x = 17 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + -2x = 17 + 0 15 + -2x = 17 Add '-15' to each side of the equation. 15 + -15 + -2x = 17 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = 17 + -15 -2x = 17 + -15 Combine like terms: 17 + -15 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| 3.1q-5.5-4.7q=-2.6q-1.9 | | -12x+4=8x-(-6) | | (2x-5)(4x-8)= | | 4r+4r=72 | | 4x+6m= | | 40x=5x | | 6-a+1+4a^2+4a^2+2a= | | 4z=17-33 | | x-28=-39 | | 7(t-5)+8t=5(3t+2)-8 | | y^4+1=0 | | 3x-1=-5x+7 | | -3x+12=18x+5 | | 3x+y=700 | | 4x=-28x-3 | | -5-3p+4=36 | | 12x+21=9x | | -(5y+3)-(-4y-6)=0 | | (m-7)(x)=4 | | 13+0.05x-30=19.50 | | 9-.5x=12x | | 6x=.75(3x-5) | | 3x-.5=6x+4 | | 25=25+x | | x^8+6x^7= | | 6a-4=-22 | | 4a-18=6 | | 8x-4(-5-2)=12a | | -5a+10=-5 | | -2a-6=12 | | 2x^2=6x+3 | | 3x^2-10x-2=0 |